2001
DOI: 10.1093/clinchem/47.7.1166
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray Tandem Mass Spectrometry for Analysis of Acylcarnitines in Dried Postmortem Blood Specimens Collected at Autopsy from Infants with Unexplained Cause of Death

Abstract: Background: Deaths from inherited metabolic disorders may remain undiagnosed after postmortem examination and may be classified as sudden infant death syndrome. Tandem mass spectrometry (MS/MS) may reveal disorders of fatty acid oxidation in deaths of previously unknown cause. Methods: We obtained filter-paper blood from 7058 infants from United States and Canadian Medical Examiners. Acylcarnitine and amino acid profiles were obtained by MS/MS. Specialized interpretation was used to evaluate pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(116 citation statements)
references
References 30 publications
5
109
0
2
Order By: Relevance
“…15 The largest study of infants with unexplained cause of death to date found a very small proportion of such cases to be due to MCAD, constituting 0.25:100,000 live births. 16 Because it is unclear how to combine this rate with the estimated rate of clinical MCAD diagnoses derived from English data, in the base case analysis, we conservatively assume that all undi-agnosed MCAD cases in the absence of screening are asymptomatic.…”
Section: Diagnosis Rates In the Absence Of Ms/ms Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…15 The largest study of infants with unexplained cause of death to date found a very small proportion of such cases to be due to MCAD, constituting 0.25:100,000 live births. 16 Because it is unclear how to combine this rate with the estimated rate of clinical MCAD diagnoses derived from English data, in the base case analysis, we conservatively assume that all undi-agnosed MCAD cases in the absence of screening are asymptomatic.…”
Section: Diagnosis Rates In the Absence Of Ms/ms Screeningmentioning
confidence: 99%
“…In the model, these infants represent 63% of all cases observed with screening. If it is assumed that the infant mortality rate of 0.25:100,000 16 can be directly combined with base case data, in the absence of screening, one would expect 25% of MCAD cases to not be diagnosed with the disorder despite the presence of symptoms. We incorporate this figure into our best estimate result.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…These samples were stored at +4 C until analysed. Free carnitine and acylcarnitine were measured from dried filter paper blood and urine spots using electrospray tandem mass spectrometry (Micromass, Manchester, UK) as previously described [24,25].…”
Section: Methodsmentioning
confidence: 99%
“…Total long-chain ACs (acyl chains >10 carbons) circulate in plasma, with reported concentrations ranging between 1 and 4 μmol/L, 33,[80][81][82] and their levels can reach to 10-30 μmol/L under certain metabolic conditions. [83][84][85][86] Long-chain ACs are lipid metabolites with a hydrophobic side chain and a free amine like sphingosine (Figure 4), but they belong to the long-chain AC family which plays an important role in energy metabolism through mitochondrial β-oxidation of fatty acids. 87 The acylcarnitines and Co-A are produced by the reaction in which acyl moieties are transferred to carnitine from acyl-CoA by carnitine palmitoyl transferase-I (Figure 3, Figure S1, Table S2).…”
Section: Ac Metabolismmentioning
confidence: 99%